MALDI-TOF-MS IDENTIFIED RHODOCOCCUS HOAGIE BACTERAEMIA IN AN IMMUNOCOMPROMISED PATIENT - Silvia Hees de Carvalho,; Rodrigo Medrado Pereira Lopes,; Kroon, Erna Geessien; Izabela Voieta da Silva Teixeira,; Nina Lélia Caetano Corrêa, (Journal of Ayub Medical College Abbottabad, 2023)
Rhodococcus hoagie, previously referred to as R. equi, is a Gram-positive intracellular coccobacillus that belongs to the Nocardiaceae family. This multi-host pathogen causes infections in farm animals, particularly foals, but also in immunosuppressed patients, mainly individuals treated with high doses of corticosteroids, subjected to organ transplant, or infected with human immunodeficiency virus Objectives of the study are to report a bloodstream infection in an immunocompromised patient. Immunocompromised patients with advanced HIV who presented bloodstream infection, residing in an urban setting and having undertaken no trips to the countryside or elsewhere during the COVID-19 pandemic. Blood culture by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) was done in order to identify the bacteria. The immunocompromised female patient presented bloodstream infection by Rhodococcus hoagie, which was identified using MALDI-TOF-MS. R. hoagie can cause a severe infection with a high mortality rate if prompt treatment with a combination of antibiotics is not established. A high level of suspicion is required to establish the diagnosis, as it may be misdiagnosed as pulmonary tuberculosis. On gram stain, R. hoagie may appear as beaded to solid staining coccobacilli, which can be dismissed as a "diphtheroid" contaminant. The infection was identified using MALDI-TOF-MS